2016
DOI: 10.1016/j.jes.2015.12.021
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assessment of thyroid hormone receptor activity of four organophosphate esters

Abstract: Previous animal experiments have implied that organophosphate esters (OPEs) have a disruption effect on the thyroid endocrine system. However, knowledge of the toxicological mechanism remains limited. In this study, the activities of four OPEs have been characterized against the thyroid hormone (TH) nuclear receptor (TR) using two in vitro models, with the aim of evaluating their toxicity mechanisms towards the TR. The results of a TH-dependent cell proliferation assay showed that tris(2-chloro-1-(chloromethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Differences in the polarity and functional groups of OPEs have the key influences on their interaction with organisms. 2,26,27 Therefore, it is expected that information on the interaction between plant biomacromolecules and OPEs would be very helpful in elucidating the molecular mechanisms of accumulation and transformation of OPEs in plants. Plant nonspecific lipid transfer proteins (nsLTPs) are biomacromolecules in all terrestrial plants and provide the key sites for lipid binding.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Differences in the polarity and functional groups of OPEs have the key influences on their interaction with organisms. 2,26,27 Therefore, it is expected that information on the interaction between plant biomacromolecules and OPEs would be very helpful in elucidating the molecular mechanisms of accumulation and transformation of OPEs in plants. Plant nonspecific lipid transfer proteins (nsLTPs) are biomacromolecules in all terrestrial plants and provide the key sites for lipid binding.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This cell line has been used widely to study renal toxins and subsequent changes in kidney-specific markers [35] , [36] , [37] , although other studies have shown the utility of these cells to be more limited [38] . In the only other report of TDCPP in kidney-derived cells, 100 μM TDCPP (but not lower concentrations) decreased cell growth and viability in TR-transfected HEK 293 cells, although the results in non-transfected cells were not shown [20] . Several reports have characterized the effects of TDCPP in non-kidney human cell types [17] , [18] , [19] , [21] .…”
Section: Discussionmentioning
confidence: 69%
“…To study TDCPP toxicity, the use of a cell culture model is powerful because of the degree of control for dose, duration, and target types. Several studies of TDCPP toxicity have been reported from culture model systems, but only a few of these used human cells [17] , [18] , [19] , [20] , [21] . Of the human cell studies, only Ren and colleagues utilized cells that were derived from the kidney, although they were used mainly as a transfection system to test organohalogens on thyroid hormone receptor (TR) signaling.…”
Section: Introductionmentioning
confidence: 99%
“…TPP, one of the typical emerging contaminants, had been identified as one of the potential endocrine-disrupting compounds that affect thyroid hormone levels. , TR was considered as the important targets involved in the chemical perturbations of thyroid disruption. ,,,, However, no AOP had been structured to describe the causal sequences from TR activation (an MIE) to transcriptomic changes, cellular phenotypes, and diseases in AOP Wiki. Therefore, more research about the potential human health effects of TPP needs to be conducted.…”
Section: Discussionmentioning
confidence: 99%